(untitled) (Colombia Medica, 2012)
Orbital teratoma is a rare tumor composed of tissue derived from the three germinal layers, it usually occurs in otherwise healthy newborns as a fluctuating mass in orbit, with extreme proptosis and periorbital deformity. There are few reports in literature about this topic; we present a case report with severe stretching and deformity of periocular tissue, which underwent enucleation and careful removal of the tumor, properly sparing the eyelids and other structures in the anophthalmic cavity to fit an ocular prosthesis. It did well, improving the patient’s cosmetic appearance and preserving his orbitofacial development. Even though in many cases it is not possible to preserve visual function in patients with congenital orbital teratoma, it is equally important to achieve the best possible cosmetic result.